Sedentary Behavior and Health: Update from the 2018 Physical Activity Guidelines Advisory Committee - Katzmarzyk, Peter T; Powell, Kenneth E; Jakicic, John M; Troiano, Richard P; Piercy, Katrina; Tennant, Bethany (Medicine and science in sports and exercise, 2019)
To provide an overview of relationships between sedentary behavior and mortality as well as incidence of several noncommunicable diseases and weight status reported in the 2018 Physical Activity Guidelines Advisory Committee Scientific Report (2018 PAGAC Scientific Report), and to update the evidence from recent studies. Evidence related to sedentary behavior in the 2018 PAGAC Scientific Report was summarized, and a systematic review was undertaken to identify original studies published between January 2017 and February 2018. The 2018 PAGAC Scientific Report concluded there was strong evidence that high amounts of sedentary behavior increase the risk for all-cause and cardiovascular disease (CVD) mortality and incident CVD and type 2 diabetes. Moderate evidence indicated sedentary behavior is associated with incident endometrial, colon and lung cancer. Limited evidence suggested sedentary behavior is associated with cancer mortality and weight status. There was strong evidence that the hazardous effects of sedentary behavior are more pronounced in physically inactive people. Evidence was insufficient to determine if bout length or breaks in sedentary behavior are associated with health outcomes. The new literature search yielded seven new studies for all-cause mortality, two for CVD mortality, two for cancer mortality, four for type 2 diabetes, one for weight status, and four for cancer; no new studies were identified for CVD incidence. Results of the new studies supported the conclusions in the 2018 PAGAC Scientific Report. The results of the updated search add further evidence on the association between sedentary behavior and health. Further research is required on how sex, age, race/ethnicity, socioeconomic status, and weight status may modify associations between sedentary behavior and health outcomes.